A narrowly endemic species of Begoniaceae: rediscovery, distribution and conservation of Begonia jocelinoi. Issue 6 (18th November 2022) - Paglia, Isis; Luber, Jaquelini; Mansano, Vidal de Freitas; Freitas, Leandro
Abstract: Begonia jocelinoi Brade (Begoniaceae) is a threatened species, endemic to a small locality in the Brazilian Atlantic Forest. The species was formerly listed as Wanted in the Red List of Endemic Flora of the state of Rio de Janeiro because it had not been recorded since 1953. After evaluating herbarium collections and conducting fieldwork during May 2019–February 2020, we report the rediscovery of a single population of 65 reproductive individuals of B. jocelinoi, along with numerous seedlings, besides a trail in Itatiaia National Park. This Park is an IUCN category II protected area that permits some tourism activities. Some individuals of B. jocelinoi showed signs of pruning following the maintenance of the trail. We recommend strategies for in situ and ex situ conservation of this narrowly endemic species, including provision of advice to tourists regarding the occurrence of threatened species, and diversion of the trail where the species occurs.